An algebra problem by Aswad Hariri Mangalaeng

Algebra Level 2

0 -1 + 2 - 3 + 4 - ... - 2013 + 2014 =. . .


The answer is 1007.

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

6 solutions

Chuong Thanh
Oct 31, 2014

Forget the 0 so from the number -1 to the number 2014 has 2014 numbers, each pair of successive numbers (e.g -1 + 2, -3 + 4, ..., -2013 + 2014) is always equal to 1. Since 2014 numbers has 1007 pairs of successive numbers (2014/2) that each pair of successive numbers is equal to 1, the sum of terms will be 1007 x 1 = 1007!!!!

yeah, good job.. :)

Aswad Hariri Mangalaeng - 6 years, 7 months ago

Nice.. Super solving

Joshua R - 6 years, 6 months ago
Ben Payne
Nov 2, 2014

The voices in my head told me it was 1007.

Parveen Soni
Oct 31, 2014

we can write each term as sum of 1 and previous number
like 2=1+1 and 2014=1+2013
forget the 0 and total number of terms are 2014 and two terms result as single 1
Thus there will be 2014/2 terms of 1 i.e (1+1+1.............+1 (total 1007) )
hence answer will be 1007x1=1007



yeah, good job.. :)

Aswad Hariri Mangalaeng - 6 years, 7 months ago
Mohammad Khaza
Aug 12, 2018

for even/odd numbers,the summation is = n 2 =\frac{n}{2} ( 2 a + ( n 1 ) d ) (2a+(n-1)d)

for even,n=1007;a=2;d=2

for,odd,n=1007;a=1;d=2

and then, bigger value-smaller value = 1007 \text{bigger value-smaller value}\ =1007

Palash Som
Nov 14, 2014

here we can see that odd nos. are being subtracted from the even nos.

therefore sum of all even nos. - sum of all odd nos.

formula : for sum off n odd nos . = n^2

formula for sum of n even nos. = n(n+1)

= putting the values we get = 1007(1007+1) - 1007*1007

= 1015056 - 1014049

= 1007 :-)

Ceesay Muhammed
Nov 12, 2014

0-1+2-3+4-5+6-7+.................-2013+2014 since 0-1+2-3+4-5 can be written as (0-1)+(2-3)+(4-5)=-1-1-1=-3 this is the same as -((5+1)/2) if we do the sum up to -7, we get the answer as -4, which is -((7+1)/2). so you can see a pattern. In that sense, we can conclude that if we stop at -2013, that is if we do the sum till -2013, ie 0-1+2-3+4-5+................+2012-2013, this adds up to -((2013+1)/2)=-1007. The required sum is 0-1+2-3+4-5+6-7+................+2012-2013+2014=-1007+2014=1007.

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...